Training intensity and stroke variables during interval training at critical swimming velocity in national-level swimmers - Funai, Y.; Taba, S.; Kanegawa, Y.; Taimura, A.; Matsunami, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Critical swimming velocity (CV), calculated as the slope of the regression line between distance and time, have been used as an index for setting intensity aerobic training. In aerobic interval training (IT), physiological and biomechanical responses are considered to vary depending on swimming distance per repetition (Hellard et al., 2010). This study examined the effects of the swimming distance per repetition on the training intensity and stroke variables in IT using the CV. METHODS Eleven national-level collegiate swimmers (19.45 ± 1.04 years) participated in an all-out 200 and 400 m front crawl swims to determine the CV. Thereafter, the participants performed 5 × 400, 10 × 200, and 20 × 100 m front crawl swims at the CV (400, 200, and 100-m IT, respectively), and each bout was separated by 60, 30, and 15 s of passive rest, respectively. Blood lactate concentration was measured after each test, and heart rate and rated perceived exertion were assessed during the rest period every 400 m. Stroke rate and stroke length were measured every 50 m, and the mean value was calculated for every 400 m. RESULTS The mean calculated CV value was 1.44 ± 0.07 m/s. The blood lactate concentration was significantly lower in the 100-m IT (3.4 ± 1.9 mmol/l) than the 400 and 200-m IT (6.4 ± 2.6 and 5.3 ± 3.2 mmol/l, p < 0.05). The heart rate in 100-m IT was significantly lower than the 400-m IT after 800 m (p < 0.05) and did not differ across measurement points (p > 0.05). The stroke rate and stroke length were significantly different between the 400 and 100-m IT (p < 0.05) but did not differ between the 200 and 100-m IT (p > 0.05) for all measurement points. DISCUSSION Regarding the intensity of IT using the CV, 400 and 200 m were considered overload, while 100 m was considered the optimum intensity. Nevertheless, the propulsive efficiency per stroke of IT using CV for 200 m may not be different from 100 m.